TOWARDS ACTIVATION OF THE EMPATHIC RESOURCES DURING TERMINAL CARE - AN ART AND/OR A NECESSITY? - Vanina Mihaylova; Mariana Liochkova; Iliya Bivolarski; Miglena Tarnovska; Dimitar Shopov; Adolf Alakidi (Peytchinski Publishing, 2021)
A brief historical-analytical review of the origin, essence, and development of empathy has been made. The theoretical measurements in the study of the empathic ability are subject to special attention. On the basis of topical definitions of the concept, the application of the approach in different spheres of life, and more specifically in medical practice, has been discussed. The types of communicative behavior in primary medical practice have been differentiated. A theoretical, applied method of communication intervention within the framework of operationalization and scaling of the empathic interaction is proposed. On the basis of the assumption of a genetically determined property of co-experience, the preconditions for the establishment of optimal interpersonal context upon exchange of information between the physician and the patient and making medical decisions have been outlined. Led by the so systematized and analyzed models and considering the specification of the transformed and activated empathic resources in cases of terminal conditions, an attempt has been made for the presentation of an extensive type of empathic interaction, applied in palliative medicine. The outlining of key messages in cases of terminal conditions in the specified model is complex and at the same time an open, dynamic process, requiring adaptation and enrichment with parameters of religious, ethnical and social nature, and other factors of psychological, spiritual and bio-ethical type in the complex interactive space of palliative medicine.